Wider applications for Lean: An examination of the fundamental principles within public sector organisations. Issue 5 (2014) - ,; ,; ,
Abstract : Purpose – The lean enterprise model has been adopted in a wide range of industries beyond its origins in the motor industry. To achieve this there has been a considerable extension of the lean concept outside high‐volume repetitive manufacture. The purpose of this paper is to present an in‐depth study of the application of lean within the British Royal Air Force. It offers a number of new insights which have implications for the future development and adoption of lean in service contexts, and the public sector in particular.Design/methodology/approach – To illustrate the issues of application of lean outside automotive, this paper considers the adoption of the lean concept by the Tornado joint integrated project team within the UK Ministry of Defence. A review of methods of application of lean used within Tornado are studied. The paper considers how the fundamental principles of lean apply in this environment and how, considering these principles, methods of implementation should be modified.Findings – This paper finds that the five lean fundamental principles apply in Tornado but they need to considered specifically within the public service context particularly the pull principle. Hence the authors offer three propositions relating to the use of the lean principles of value, waste, flow and pull in the public sector, and one for perfection only relating to military organisations.Originality/value – This paper makes an important contribution by demonstrating that lean can be successfully applied, in a public service context, with only modest modifications to its core principles, principally about how customer demand (pull) is managed. The implication of this finding demonstrates that to be adopted successfully, lean must be adapted to its context and the lean principles need to be reviewed too. Acknowledgements : Thanks to Wing Commander (Retd) Paul Hudson formerly of RAF Tornado JIPT now Lockheed Martin for his contribution to this research.